EBSD-coupled indentation: nanoscale mechanics of lithium metal. (December 2022) - Aspinall, Jack; Armstrong, David E.J.; Pasta, Mauro
Abstract: The fracture of ceramic solid electrolytes, driven by the plating of lithium within cracks, has been identified as one of the fundamental issues to successfully develop solid-state batteries. Understanding the mechanics of lithium at the nanoscale is therefore essential. In this work, the elastic and plastic properties of lithium are measured by nanoindentation within an electron microscope. Lithium metal samples are characterized by electron backscattered diffraction before and after indentation to understand the dependence of the mechanical properties on crystallographic orientation and determine the stiffness tensor components, moduli, and Poisson's ratio using a method first proposed by Vlassak and Nix. The measured stiffness tensor components are C11 = 13.3, C12 = 11.2, and C44 = 8.8 GPa. Hardness measurements show a clear size effect with hardness in excess of 100 MPa observed for indent depths below 300 nm, which could contribute toward observed lithium filament propagation. Graphical abstract: Image 1 Highlights: Novel method to prepare a fresh lithium surface with nanoscale roughness for electron backscattered diffraction mapping. Stiffness tensor measured from electron backscattered diffraction-correlated nanoindentation. Quantified size-dependent hardness of pure lithium.